Implementasi Pembelajaran Tematik Berbasis Kurikulum 2013 (Studi Multikasus Di MI Darut Taqwa Sengonagung Purwosari Pasuruan) - Asmawi Asmawi (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2021)
This study aims to describe and analyze: 1) the implementation of the 2013 Curriculum learning at Madrasah Ibtidaiyah Darut Taqwa Sengonagung Purwosari Pasuruan. 2) school efforts in order to successfully implement the 2013 Curriculum at Madrasah Ibtidaiyah Darut Taqwa Sengonagung Purwosari Pasuruan. 3) the supporting and inhibiting factors for the implementation of thematic learning based on the 2013 Curriculum at Madrasah Ibtidaiyah Darut Taqwa Sengonagung Purwosari Pasuruan. Based on data analysis and discussion, it can be concluded: 1) Implementation of 2013 Curriculum learning includes planning, implementation, and assessment of 2013 Curriculum-Based Thematic Learning 2) Implementing mental, moral, physical and artistic guidance to educators on matters relating to attitude and character. 3) Factors supporting and inhibiting the implementation of curriculum-based thematic learning.